Association between Anemia and First-time Febrile Seizure: A Case Control Study - Handoyo (PT Kalbe Farma Tbk., 2018)
Background. Febrile seizure is the most frequent neurological disorder in childhood. Some studies report association between anemia and febrile seizure. Even though anemia is highly prevalent in Indonesia, only one study assessed this association. Objective. To compare the hemoglobin level in children with febrile seizure and febrile children without seizure, and to assess the relationship between anemia and febrile seizure. Method. This retrospective case control study used medical record of febrile children aged 6 months to 3 years old hospitalized at Landak General Hospital from May 2016 to April 2017. Hemoglobin level from first blood workup then compared between fifty children with first-time febrile seizure (case group) and a hundred febrile children without seizure (control group). Results. Hemoglobin level was lower in case group compared to control group (p =0.000). Children with febrile seizure were more likely to be anemic compared to febrile children without seizure [OR 6.73 with 95% CI 3.18 to 14.26]. Conclusion. There is significant difference of mean hemoglobin among children with febrile seizure compared to febrile children without seizure. Children with febrile seizure were six times more likely to have anemia. Latar belakang. Kejang demam adalah gangguan neurologi yang paling sering ditemukan pada anak. Beberapa penelitian menemukan hubungan antara anemia dan kejang demam. Meskipun prevalensi anemia tinggi di Indonesia, hanya satu studi meneliti tentang hubungan ini. Tujuan. Untuk membandingkan kadar hemoglobin pada anak dengan kejang demam dan anak demam tanpa kejang, serta menilai hubungan antara anemia dan kejang demam. Metode. Penelitian retrospektif kasus kontrol, menggunakan data rekam medis anak dengan demam berusia 6 bulan hingga 3 tahun yang dirawat di RSUD Landak dari bulan Mei 2016 hingga April 2017. Kadar hemoglobin dari pemeriksaan sampel darah pertama pada 50 anak demam dengan kejang pertama kali (kelompok kasus) dibandingkan dengan pemeriksaan 100 anak demam tanpa kejang (kelompok kontrol). Hasil. Rerata kadar hemoglobin lebih rendah pada kelompok kasus dibandingkan kelompok kontrol (p =0.000). Anak demam dengan kejang cenderung dalam kondisi anemia dibandingkan anak demam tanpa kejang [OR 6.73, 95%IK 3.18 - 14.26]. Simpulan. Terdapat perbedaan signifikan rerata kadar hemoglobin antara anak demam dengan kejang dibandingkan dengan anak demam tanpa kejang. Anak demam dengan kejang memiliki kecenderungan 6 kali lipat menderita anemia.